중국의 쌀 수급 현황과 전망 - 정정길 (한국농촌경제연구원, 2003)
Situation and Prospect for Rice Demand-Supply in China The purpose of this paper is to find out the current situation of rice industry in China and to forecast future rice trade between Korea and China through analyzing international competitiveness of Chinese rice and changes in trade environment. Based on these findings, it is aimed to provide fundamental materials needed to draw out rice related policy in preparation for WTO rice negotiations. China is the biggest country in producing rice in the world. Its outstanding position in terms of rice production and export is evident. In recent years, Japonica-breed rice farming area has rapidly increased in China and it takes up 25% of total rice farming area in China. Japonica-breed rice in China combines competitiveness in both price and quality, so that its influence on Korea's rice industry will be further increasing. In particular, rice produced in the Northeastern part of China has relative advantages in terms of quality since it is based on Japanese rice breed. Besides, the production environment like climate is proper for producing high-quality rice such as environment-friendly and organic rice. Compared with other countries, China also has more advantageous position due to geographical contiguity to Japan and Korea, which are major rice import countries. The Chinese government has begun to promote the strategy of export expansion such as construction of environment-friendly Japonica-breed rice production area since it viewed increasing potential in export to Japan and Korea. This export-driven policy is expected to have a great effect on the rice industry in Korea. Therefore, it is imperative for the Korean government to take measures to protect and develop the domestic rice industry. Researchers: Chung Chung-Gil and Sung Myung-Hwan et al. E-mail address: cgchung@krei.re.kr
Keywords: 중국 쌀 식량정책 중국의쌀